The Influence of Company Performance Toward Stock Price of PT XL Axiata Tbk From 2008 to 2014 - Abditama, Hidayat Ihsan; Damayanti, Sylviana Maya (Journal of Business and Management, 2015)
Abstract. Nowadays, Information and telecommunication sector had been increased highly. It is essential for the investors to make the profitable investment like stock market investment value. It is becoming the main reason to makes the company managers more intensively to catch these opportunity and create the creative and comprehensive planning for good company performance that increase the value of companies itself. One of that is the PT. XL Axiata Tbk. that ever success be the biggest operator in second position in Indonesia. These studies explore the influence of company performance toward stock price of PT. XL Axiata Tbk. in the form of financial ratios assessment. This study examines seven financial ratios that represent five basic category of financial ratio. There are Profitability, Liquidity, Activity, Debt, and Market Ratio. ROA, Current, Asset Turnover, DER, EAR, PER and Dividend Payout ratio was used as independent variable. Whereas stock price becoming the dependent variable. This study use the balance sheet income statement and capital adequacy report each four quarter during period 2008 to 2014 as well as implementing regression time series analysis method. This study indicate that only ROA that has positive significant relationship toward stock price. And the other way, DER, EAR and PER has negative significant relationship toward stock price. This study also indicate that ROA, PER and DPR is in step with profit movement, and Current, Asset turnover, DER and EAR is in step with revenue movement of PT. XL Axiata Tbk. from 2008 to 2014.Ã‚Â Keywords: Company Performance, Financial Ratio, Linear Regression Time Series, Telecommunication, XL Axiata